Some questions of the terms used in criminal legal proceedings. (Journal of actual problems of jurisprudence, 2016)
It is very important to understand correctly the legal nature of terms which are used in a criminal sudoprizvodstvo. This article is devoted to formation of some concept and terms in criminal legal procee- dings. Besides, the analysis of different views of scientists on this problem is given.
Keywords: person; personality; legal entities; subjects; participants of legal proceedings; etc.